A Functional Flatbread (Bazlama): High in Beta-Glucan and Plant-Based Protein Content - Beyaz, Seda; Cetiner, Buket; Ozkan, Kubra; Sagdic, Osman; Sestili, Francesco; Koksel, Hamit (MDPI, 2025)
This study focused on developing a functional bazlama with a lower glycemic index (GI) that is high in beta-glucan and rich in plant-based protein. Functional bazlama samples were produced by supplementing bread wheat flour with high beta-glucan content hull-less barley flour and high protein content lentil flour (15%, 30%, and 45%). Additionally, mixed bazlama samples (Mix1, Mix2, Mix3, and Mix4) were produced by supplementing them with both barley and lentil flours. The results showed that 3 g of beta-glucan could be provided from the bazlama sample and supplemented with 45% barley flour, which meets the threshold to carry health claims. Supplementing with 30% and 45% lentil flour increased the protein content of the bazlama samples to a level qualifying them as a high protein. The control bazlama had a high GI, while samples supplemented with 30% and 45% barley or lentil flour and all mixed bazlama samples had medium GI values, and Mix2 had the lowest GI value among all bazlama samples. Also, as the supplementation levels of barley and lentil flour increased, the phenolic contents and antioxidant capacities of the bazlama samples increased. The results of the present study indicate that barley and lentils can be used as an ingredient in traditional flatbreads to obtain products with better functional and nutritional properties.
Keywords: hull-less barley; lentils; traditional bread; phenolics; antioxidants; glycemic index; functional foods; ANTIOXIDANT ACTIVITY; MOLECULAR-WEIGHT; WHEAT-FLOUR; BREAD; LENTIL; DIGESTIBILITY; QUALITY; BLENDS; Food Science & Technology